2022
DOI: 10.3390/dj10040057
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Student Clinical Communication Skills in Dental Education—A Narrative Review

Abstract: Dental student training in clinical communication skills and behavioral aspects of treatment are lauded as clinically meaningful in the dental education literature. However, many dental school curricula still only provide didactic, one-time coursework with multiple choice examination assessment and little or no student skill-activating activities. This article aims to review literature relevant to optimizing clinical communication and behavioral skills in dental education. The review summarizes findings of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
0
8
0
4
Order By: Relevance
“…Having a tool such as the CARE measure validated in Spanish and in the context of dentistry is a necessary step to develop new lines of research into the acquisition of interpersonal skills in this field, and to be able to carry out educational interventions aimed at training in relational empathy. This need is justified in view of the high percentages of dental anxiety in the population, as well as the vulnerability that can be generated in patients due to the working position in the dental chair 16 …”
Section: Discussionmentioning
confidence: 99%
“…Having a tool such as the CARE measure validated in Spanish and in the context of dentistry is a necessary step to develop new lines of research into the acquisition of interpersonal skills in this field, and to be able to carry out educational interventions aimed at training in relational empathy. This need is justified in view of the high percentages of dental anxiety in the population, as well as the vulnerability that can be generated in patients due to the working position in the dental chair 16 …”
Section: Discussionmentioning
confidence: 99%
“…Interactive pedagogical techniques include role-playing, simulated patient encounters, interactions with standardized patients (SPs), actual patient interviews, small-group activities, and video-based exercises. A systematic review revealed that the fundamental principles for effective communication training encompass active learning strategies, such as incorporating practical exercises, clinically relevant scenarios, self-assessment tools for students, use of videotapes, and involvement of patient actors [ 11 , 12 ]. However, dental school curricula often have insufficient skill-activating programs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review revealed that the fundamental principles for effective communication training encompass active learning strategies, such as incorporating practical exercises, clinically relevant scenarios, self-assessment tools for students, use of videotapes, and involvement of patient actors [ 11 , 12 ]. However, dental school curricula often have insufficient skill-activating programs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Students' satisfaction with the clinical and social skills acquired during the educational process is a possible indicator of the quality of the study programme. 8,9 One of the methods to evaluate the educational system is to survey the students as they fully experience the impact of education. 10 Therefore, a cross-sectional study was conducted to determine satisfaction with the quality of education among dentists and dental students in Croatia.…”
Section: Introductionmentioning
confidence: 99%
“…For dental students to be excellent and successful dentists after graduation, they should gain sufficient clinical experience during their studies by receiving adequate training in clinical, technical, analytical, communication and management skills in addition to theoretical knowledge 7 . Students' satisfaction with the clinical and social skills acquired during the educational process is a possible indicator of the quality of the study programme 8,9 . One of the methods to evaluate the educational system is to survey the students as they fully experience the impact of education 10 …”
Section: Introductionmentioning
confidence: 99%